1977
DOI: 10.1159/000225175
|View full text |Cite
|
Sign up to set email alerts
|

Second Malignancies in Patients with Multiple Myeloma

Abstract: Seven patients with multiple myeloma who developed a second neoplasm are presented. There were four patients with acute leukemia and three patients with non-hematologic neoplasms. The patients with acute leukemia were among the longest survivors (median duration ≈ 72 months) and the response to anti-leukemic therapy in these patients was generally poor. Of the three patients with non-hematologic neoplasms, one patient was observed with simultaneous renal cell carcinoma and the other two patients developed aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…reported that, in 1027 patients diagnosed with multiple myeloma, the proportion of secondary hematologic malignity was 0.7% and the proportion secondary solid malignancy was 1.9% [8]. As we mentioned earlier, malignancies synchronized with multiple myeloma have been reported before [1][2][3][4][5]. But it was not included medullary thyroid carcinoma which occurs extremely rare, to our knowledge there are no prior reports of this case.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…reported that, in 1027 patients diagnosed with multiple myeloma, the proportion of secondary hematologic malignity was 0.7% and the proportion secondary solid malignancy was 1.9% [8]. As we mentioned earlier, malignancies synchronized with multiple myeloma have been reported before [1][2][3][4][5]. But it was not included medullary thyroid carcinoma which occurs extremely rare, to our knowledge there are no prior reports of this case.…”
Section: Discussionmentioning
confidence: 67%
“…The co-existence multiple myeloma and another cancer such as renal cell carcinoma, lung, gastric carcinoma, colon, prostate, breast, bladder, uterus, and liver have been reported severally in literature [1][2][3][4][5], but medullary thyroid carcinoma (MTC) as a second malignancy with multiple myeloma is an extremely rare case which seems has not been reported before, here we are presenting a case with these two types of cancer. A 54-year-old male with diabetes history presented on 17th November 2013 with complaints of severe bone pain on his shoulder and vomiting.…”
Section: Introductionmentioning
confidence: 98%
“…Although the immune deficiencies forming part of the original pathologic process in patients with multiple myeloma or AIDS may also predispose them to secondary malignancies [22,23], there is no solid evidence that immune deficiency caused by NHL is a predisposing factor for AML. In the present case, firm evidence was also lacking that AML blasts and lymphoma cells had the same origin, since chromosomal analysis of the lymphoma cells was not successful.…”
Section: Discussionmentioning
confidence: 99%
“…The relation of multiple myeloma with gastric MALT type lymphomas [248][249][250][251][252][253][254] was identified many years before H. pylori was known. Today, it is known that in MALT lymphoma, H. pylori antigens can also stimulate plasma cells.…”
Section: Plasma Cell Dyscrasiasmentioning
confidence: 99%